Toxicomethylomics revisited: A state-of-the-science review about DNA methylation modifications in blood cells from workers exposed to toxic agents - Jiménez-Garza, Octavio; Ghosh, Manosij; Barrow, Timothy M.; Godderis, Lode (Frontiers in Public Health, 2023)
Introduction Epigenetic marks have been proposed as early changes, at the subcellular level, in disease development. To find more specific biomarkers of effect in occupational exposures to toxicants, DNA methylation studies in peripheral blood cells have been performed. The goal of this review is to summarize and contrast findings about DNA methylation in blood cells from workers exposed to toxicants. Methods A literature search was performed using PubMed and Web of Science. After first screening, we discarded all studies performed in vitro and in experimental animals, as well as those performed in other cell types other than peripheral blood cells. Results: 116 original research papers met the established criteria, published from 2007 to 2022. The most frequent investigated exposures/labor group were for benzene (18.9%) polycyclic aromatic hydrocarbons (15.5%), particulate matter (10.3%), lead (8.6%), pesticides (7.7%), radiation (4.3%), volatile organic compound mixtures (4.3%), welding fumes (3.4%) chromium (2.5%), toluene (2.5%), firefighters (2.5%), coal (1.7%), hairdressers (1.7%), nanoparticles (1.7%), vinyl chloride (1.7%), and others. Few longitudinal studies have been performed, as well as few of them have explored mitochondrial DNA methylation. Methylation platforms have evolved from analysis in repetitive elements (global methylation), gene-specific promoter methylation, to epigenome-wide studies. The most reported observations were global hypomethylation as well as promoter hypermethylation in exposed groups compared to controls, while methylation at DNA repair/oncogenes genes were the most studied; studies from genome-wide studies detect differentially methylated regions, which could be either hypo or hypermethylated. Discussion Some evidence from longitudinal studies suggest that modifications observed in cross-sectional designs may be transitory; then, we cannot say that DNA methylation changes are predictive of disease development due to those exposures. Conclusion Due to the heterogeneity in the genes studied, and scarcity of longitudinal studies, we are far away from considering DNA methylation changes as biomarkers of effect in occupational exposures, and nor can we establish a clear functional or pathological correlate for those epigenetic modifications associated with the studied exposures.